A New Method for the Economic Laws of Extinction Using the Fox-Wright-type Function - Ibrahim, Rabha W.; Hadid, Samir B. (Journal of Science and Technology, 2018)
In this note, we deal with the possibility of optimal economic extinction. We employ the Fox-Wright-type function to characterize the probability of transference from optimal selection to the economic laws of extinction. For the extinction, we shall utilize the fractional Poisson process.